As-vacancy complex in Zn-diffused GaAs: Positron lifetime spectroscopy study. (1st April 2017) - Elsayed, M.; Krause-Rehberg, R.
Abstract: Positron annihilation lifetime spectroscopy is applied to study the point defects formed upon Zn diffusion in semi-insulating GaAs. The diffusion was performed by annealing the samples at 950 °C for different times under different As vapor pressures. Deep and shallow positron traps were observed by lifetime spectroscopy. Zn acceptors are assumed to act as shallow traps. A complex containing the As vacancy and Zn atoms is suggested to be the deep positron traps. The observation of As vacancy complexes is elucidated by studying the influence of As vapor pressure applying the mass action law of thermodynamics of point defects. Graphical abstract: